Fatal outcome of isolated patients who suffered an in-hospital cardiac arrest. (September 2022) - Haschemi, Jafer; Marc Haurand, Jean; Oehler, Daniel; Westenfeld, Ralf; Kelm, Malte; Horn, Patrick
Abstract: Aim: Isolation of patients in single-patient rooms for infection control precautions leads to less contact with medical staff. Our objective was to assess whether isolated patients who suffer an in-hospital cardiac arrest (IHCA) have lower survival as non-isolated IHCA patients. Methods: We screened for IHCA occurrence and the isolation state in 75.987 patients that had been hospitalized from 2016 to 2019 at the university hospital. Primary endpoint was survival to discharge. Neurological outcome was assessed using the cerebral performance category scale. Results: In five consecutive years, 4, 249 out of 75, 987 patients (5.6%) had to be isolated for infection control precautions. In-hospital cardiac arrest occurred in 32 (0.8%) of these isolated patients and in 410 out of 71, 738 non-isolated patients (0.6%) ( p = 0.130). Propensity score matching yielded 30 isolated and 30 non-isolated patients who suffered an IHCA, without a difference in baseline characteristics and characteristics of cardiac arrests between the groups. Only one out of 30 isolated patients (3.3%) survived to discharge after IHCA compared to 11 non-isolated patients (36.6%) (risk difference, 33.3% [95% CI, 14.9%–51.7%]. None of the 30 isolated patients were discharged with good neurological outcomes compared to nine out of 30 non-isolated IHCA patients (30%) (risk difference, 30% [95% CI, 13.6%–46.4%]). In the multivariate analysis, patient isolation was an independent predictor of poor survival after IHCA (OR, 18.99; 95% CI, 2.467–133.743). Conclusions: Isolation of patients for infection control precautions is associated with considerable poorer survival and neurological outcome in case these patients are suffering an IHCA.